IMPLEMENTATION OF RESTORATIVE JUSTICE TOWARDS CRIMINAL ACTS OF ASSAULT AT THE PEMATANGSIANTAR DISTRICT PROSECUTOR'S OFFICE - Wira Afrianda Damanik; Rachmad Abduh (International Journal of Synergy in Law, Criminal, and Justice, 2026)
Restorative justice is a new approach in Indonesia that closely aligns with the principle of deliberation, the soul of the Indonesian nation. Restorative justice offers the best solution for resolving private crimes between individuals or legal entities, prioritizing the core of the crime. Abuse is an unlawful act, any act or action committed by a person that results in harm to the individual. Ordinary abuse is a legal act that stems from intent. This intent means that the consequences of an act are intended, and this is evident when the consequences are truly intended to cause pain, injury, or death. However, not all acts of hitting or other acts that cause pain are considered abuse